Evaluation of Sex Differences in the Elasticity of Demand for Nicotine and Food in Rats. Issue 6 (6th September 2019) - Chellian, Ranjithkumar; Wilson, Ryann; Polmann, Michaela; Knight, Parker; Behnood-Rod, Azin; Bruijnzeel, Adriaan W
Abstract: Introduction: Animal studies can inform policy regarding nicotine levels in tobacco products and e-cigarette solutions. Increasing the price of nicotine-containing products decreases their use, but it is unknown how the relationship between price and consumption is affected by both sex and nicotine dose. Methods: A behavioral economics procedure was used to determine the demand elasticity for nicotine in male and female rats. Demand elasticity describes the relationship between price and consumption. A high level of elasticity indicates that consumption is relatively sensitive to increases in price. The rats self-administered a low dose (0.01 mg/kg/inf) or a standard dose (0.03 mg/kg/inf) of nicotine for 9 days under a fixed-ratio (FR) 1 schedule. Then the price (FR schedule) of nicotine was increased, and a demand analysis was conducted. A similar study was conducted with palatable food pellets. Results: There were no sex differences in nicotine or food intake under the FR1 schedule. However, demand for 0.03 mg/kg/inf of nicotine was more elastic in females than males. Demand for 0.01 mg/kg/inf of nicotine and food was more elastic in males than females. Conclusions: These findings indicate that there are no differences in nicotine and food intake between males and females when the price is low. When the price of nicotine or food is increased, males maintain their old level of intake longer than females when they have access to a standard dose of nicotine, and females maintain their intake longer when they have access to a low dose of nicotine or food. Implications: This behavioral economics analysis indicates that there is no sex difference in nicotine intake when the price of nicotine is low. Increasing the price of nicotine decreases nicotine intake in a dose- and sex-specific manner. Males maintain their old level of intake longer when they have access to a standard dose of nicotine and females when they have access to a low dose. This has implications for tobacco regulatory policy. In a regulatory environment where only low nicotine-containing products are allowed, increasing the price of nicotine products may lead to a greater decrease in nicotine use in males than females.